(untitled) (Research, Society and Development, 2020)
This work aimed to evaluate the cytotoxicity of the methanolic extract of Psidium guineense against human blood cells (erythrocytes) to evaluate the toxicity potential of this plant. The study was carried out through tests on cytotoxic activity, using blood suspensions with human erythrocytes (A, B and O), different methanolic extractive tests (50, 100, 500 and 1000 µg/mL) were used for 60 minutes and quantified hemolysis by spectrophotometry at a wavelength of 540 nm. The results obtained demonstrate the methanolic extract of P. guineense in different species, suggesting low toxicity against human erythrocytes tested in vitro, this natural product being considered a viable option for the herbal medicine industry.